Use of GeoGebra in High School Mathematics: A Case of Geometric Transformation for Teaching and Learning - Niroj Dahal; Binod Prasad Pant; Indra Mani Shrestha; Netra Kumar Manandhar (Recent Progress in Science and Technology Vol. 1, 2023)
This chapter discusses how GeoGebra is used in high school mathematics classes to teach and learn geometric transformations. GeoGebra is an interactive geometry, algebra, statistics, and calculus application of mathematical software that is very important from elementary to university levels to foster mathematical experiments and discoveries. Similarly, this chapter’s contribution included several specific illustrations of transformation, including reflection, rotation, translation, and dilation, for teaching mathematics to sixteen students in one of the secondary schools in Kathmandu Valley, Nepal. This chapter discusses the use of GeoGebra in eleven episodes by subscribing to the teaching experiment as the qualitative research methodology. To help the student understand abstract concepts of transformation, we used adequate illustrations, pictures, and animations with the help of GeoGebra. The experiment’s outcome in a classroom demonstrates the value of GeoGebra in instructing and learning about transformational ideas. The results of this study indicate that if GeoGebra is used in mathematics classes, students may start to construct their own knowledge actively. In these classes, students co-operate with one another, illustrate transformational concepts, and take pride in their authority in the classroom. The traditional lecture method of teaching mathematics, which moves the focus of education from the teacher to the learner, is supported by this crucial visualizing tool.